Beneficial Effects of an 8-Week, Very Low Carbohydrate Diet Intervention on Obese Subjects. (14th March 2013) - Gu, Yunjuan; Yu, Haoyong; Li, Yuehua; Ma, Xiaojing; Lu, Junxi; Yu, Weihui; Xiao, Yunfeng; Bao, Yuqian; Jia, Weiping
Abstract : Aim . To investigate the effects of weight loss during an 8-week very low carbohydrate diet (VLCD) on improvement of metabolic parameters, adipose distribution and body composition, and insulin resistance and sensitivity in Chinese obese subjects. Methods . Fifty-three healthy obese volunteers were given an 8-week VLCD. The outcomes were changes in anthropometry, body composition, metabolic profile, abdominal fat distribution, liver fat percent (LFP), and insulin resistance and sensitivity. Results . A total of 46 (86.8%) obese subjects completed the study. The VLCD caused a weight loss of − 8.7 ± 0.6  kg (mean ± standard error (SE), P < 0.0001 ) combined with a significant improvement of metabolic profile. In both male and female, nonesterified fatty acid (NEFA) significantly decreased (− 166.2 ± 47.6   μ mol/L, P = 0.001 ) and β -hydroxybutyric acid (BHA) increased (0.15 ± 0.06  mmol/L, P = 0.004 ) after eight weeks of VLCD intervention. The significant reductions in subcutaneous fat area (SFA), visceral fat area (VFA), and LFP were − 66.5 ± 7.9  cm 2, − 35.3 ± 3.9  cm 2, and − 16.4 ± 2.4 %, respectively (all P values P < 0.0001 ). HOMA IR and HOMA β significantly decreased while whole body insulin sensitivity index (WBISI) increased (all P values P < 0.001 ). Conclusion . Eight weeks of VLCD was an effective intervention in obese subjects. These beneficial effects may be associated with enhanced hepatic and whole-body lipolysis and oxidation.